Achillea millefolium Based on Bioinformatics Studies and Toxicity Test on The Chicken Embryo - Maslichah Mafruchati (Lembaga Pengembangan Kinerja Dosen, 2025)
In Iranian Traditional Medicine, some herbs like Achillea millefolium, commonly known as yarrow, are implicated as appetite enhancers. However, there is not enough research evidence to prove their actual effect. Achillea millefolium is a dicot which belongs to the family Asteraceae. The purpose of this study was the analysis Achillea millefolium based on a bioinformatic study and toxicity test on the chicken embryo. This research method consisted of conversion of nucleotides into amino acids, analysis of the three-dimensional structure of Achillea millefolium protein, epitope and Allergen Proteins, antigens and toxins and toxicity test on the chicken embryo. In addition, this study also obtained the results of proteins that are epitope, antigenic, non-allergenic and non-toxic and toxicity test on the chicken embryo was 250 ng/egg.. Morphological description of the embryo on the 21st day after injection, at a concentration of 250 ng of Mentha piperita/egg product, an abnormal embryological picture was obtained. Chicken Embryo Weight and Body Length Measurements were carried out in chicken embryos. Need research for other species of plant.